Photochemical and Thermal Energy Transformation for Hydrogen Generation - Li, Xiaojie (Curtin University, 2020)
One of the most significant developments in photocatalytic hydrogen evolution reaction (PC-HER) is the application of graphitic carbon nitride (g-C3N4). In this PhD thesis, the influences of solar-heat on PC-HER were investigated with different nanomaterials as photocatalysts. Meanwhile, novel g-C3N4 based nanostructures, including NiO quantum dots decorated g-C3N4, single-atom Ag modified g-C3N4, and K doped g-C3N4/g-C3N4 van der Waals type II junctions, were developed, applied, and carefully studied in PC-HER processes.